Bilateral Anterior and Intermediate Uveitis with Occlusive Vasculitis as Sole Manifestation of Relapse in Multiple Sclerosis - Angelica Pedraza-Concha; Karin Brandauer; Alejandro Tello; Carlos Mario Rangel; Christian Scheib (Case Reports in Ophthalmological Medicine)
76-year-old female patient, with past medical history of relapsing-remitting multiple sclerosis manifested by retrobulbar optic neuritis in both eyes with an interval of one year between the first episode in the left eye and the one in the right eye and after three decades of remission, who consulted due to bilateral blurred and foggy vision. Subsequently, several differential diagnoses where ruled out. Diagnosis of bilateral anterior and intermediate uveitis with occlusive vasculitis attributed to a new relapse episode of multiple sclerosis was made, as the association between multiple sclerosis and intermediate uveitis is known, though the causal association is still questioned. This case shows how multiple sclerosis may only manifest with ocular involvement and exemplifies the broad spectrum of manifestations and complications, taking into account that ischemic areas from vasculitis and other comorbidities led to macular edema and unfortunately, prognosis became poorer. The complex course of the case enables emphasizing the responsibility role of the ophthalmologists in such systemic entities that may compromise the eye, in which suspicion of the disease and an adequate timing management approach is essential.